RELATIONSHIP ANALYSIS TOTAL CATCH GOMBANG CAPTURE TOOL WITH FACTOR OCEANOGRAPHY IN THE WATERS VILLAGE BUNSUR DISTRICTS RIVER APIT DISTRICT SIAK PROVINCE RIAU - Jefri Raja Kandi; T. Ersti Yulika Sari; Usman ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Survey methods performed to monitor water parameters and data haul in four stations in December 2015 in the village Bodies Bunsur districts Sungai Apit district Siak. The results of the study, the temperature ranges from 28-32°C pairs. 27-32°C subsided. Based on regression analysis does not give effect to the catch. Salinity ranges from 26-31%o pairs. 26-32%o downs. Based on regression analysis during the study provides segnifikan effect on catches. Flow velocity ranges from 0.09 - 0.12m/s tide. 12:10 - 0.14m/sec and downs. based on regression analysis found spotted and currents at low speed that gives effect to the catches segnifikan. Based on an analysis of the operation of fishing gear Gombang area. It is said to potentially be at a temperature of 29-32°C, salinity 28-32 %o, and 0.10 - 0.14m/s for speed Flow.Keywords : Free Flow, Salinity, temperature, Catch, environmental